2020
DOI: 10.3390/lubricants8120103
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Methodology for Determining the Energy Losses in Auxiliary Systems and Friction Processes Applied to Low Displacement Diesel Engines

Abstract: The problem of climate change and the reduction of fossil fuels has motivated the development of research focused on improving the efficiency of internal combustion engines. This research proposes a methodology based on mathematical models to determine the energy losses caused by auxiliary systems and friction processes in the engine. Therefore, models are proposed for calculating the energy losses in fuel injection, lubrication, and cooling system. In the same way, models are proposed for the energy losses du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 54 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…In the third case, dry and boundary are excluded, and the hydrodynamic lubrication regime in the triad is constantly provided metal-oil-metal. However, the change in the geometry of the parts reduces their strength [40,41]. In connection with these examples, the given technologies have a single character.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the third case, dry and boundary are excluded, and the hydrodynamic lubrication regime in the triad is constantly provided metal-oil-metal. However, the change in the geometry of the parts reduces their strength [40,41]. In connection with these examples, the given technologies have a single character.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The energy losses of the fuel injection system, lubrication system, and cooling system are equal to 0.61%, 0.30%, and 0.31% of the total chemical energy of the injected fuel, respectively. As far as energy losses due to friction processes are concerned, it was observed that the main losses are located in the piston and reach the maximum value [1].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous approaches have been successfully employed to enhance engine efficiency. This includes the insertion of heating waste recovery systems, combustion efficiency refinement, and scaling down frictional losses in the engine [6][7][8][9][10]. Friction reduction has been receiving considerable interest from scientists, as a cost-effective method to empower engine efficiency.…”
Section: Introductionmentioning
confidence: 99%